Redescription of Pectiniunguis gaigei (Chamberlin, 1921) from Guyana, with new distributional data and complementary descriptive notes on similar neotropical species (Chilopoda: Geophilomorpha: Schendylidae) - Pereira, Luis Alberto (Papéis Avulsos de Zoologia, 2010)
Pectiniunguis gaigei (Chamberlin, 1921) from Guyana, (Chilopoda: Geophilomorpha: Schendylidae) is here redescribed and illustrated on the basis of type material. The species is characterized by the absence of pore-field on the first sternum; presence of undivided ventral pore-fields in an uninterrupted series along the whole trunk length; parunguis of walking legs thin and pale; and last leg praetarsus as a small tubercle with numerous spines. All these combined traits are shared by three other Neotropical members of the genus (P. geayi (Brölemann & Ribaut, 1911) from Brazil; P. ducalis Pereira, Minelli & Barbieri, 1995 from Brazil; and P. roigi Pereira, Foddai & Minelli, 2001 from Ecuador), with which P. gaigei is here compared in detail. New distributional records for P. ducalis and P. geayi, together with complementary descriptive notes and new diagnoses for these species and P. roigi, are also given.